Standardization of Trading Board Lot: Effect on Price and Liquidity - Ibrahim, Nor Elliany Hawa; Mohd, Kamarun Nisham Taufil; Lee, Karren Hwei Khaw (UUM Press, 2017)
In this study we examined the announcement and implementation effect of the standardization of trading board lot event at the Kuala Lumpur Stock Exchange, which saw a reduction of the minimum trading unit from 1000 or 200 units to 100 units. The event was implemented in three stages, which affected all listed firms. Our findings showed that there were positive cumulative abnormal returns surrounding implementation days, indicating positive market reception of the new policy. The Securities Commission of Malaysia stated that the trading activities had increased significantly after implementation of the standard trading board lot. Regardless, this claim has never been verified from an academic perspective, which spurred us to compare its effects on liquidity in the pre- and post-standardization period. Our univariate tests showed that as a whole, the lot size reduction improved bid-ask spread and trading activities of stocks in Malaysia.